2023
DOI: 10.3390/microorganisms11122858
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Escherichia coli Isolated from Urinary Tract Infections from Aguascalientes, Mexico

Flor Yazmín Ramírez Castillo,
Alma Lilian Guerrero Barrera,
Josée Harel
et al.

Abstract: Uropathogenic Escherichia coli (UPEC) strains are among the leading causes of urinary tract infections (UTIs) worldwide. They can colonize the urinary tract and form biofilms that allow bacteria to survive and persist, causing relapses of infections and life-threatening sequelae. Here, we analyzed biofilm production, antimicrobial susceptibility, virulence factors, and phylogenetic groups in 74 E. coli isolated from diagnosed patients with UTIs to describe their microbiological features and ascertain their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…Table 1 summarizes the virulence factors implicated in E. coli pathogenesis and especially adhesion and biofilm formation. The role of virulence genes of E. coli in its adhesion to catheter surfaces has been reported in several studies [82,83,89,90,92,[94][95][96][97][98][99][100][101][102]. For example, Reisner et al [94] reported that 73% of E. coli strains isolated from catheterized patients expressed type 1 fimbriae.…”
Section: Escherichia Colimentioning
confidence: 98%
“…Table 1 summarizes the virulence factors implicated in E. coli pathogenesis and especially adhesion and biofilm formation. The role of virulence genes of E. coli in its adhesion to catheter surfaces has been reported in several studies [82,83,89,90,92,[94][95][96][97][98][99][100][101][102]. For example, Reisner et al [94] reported that 73% of E. coli strains isolated from catheterized patients expressed type 1 fimbriae.…”
Section: Escherichia Colimentioning
confidence: 98%